Exploring Coinvestment Partner Selection Strategies Using Exponential Random Graph Models - Jie Ren (Complexity, 2023)
State-owned private equity funds in China currently oversee assets worth more than 12 trillion RMB. Due to the uncertainty in the private equity market and the presence of information asymmetry, these state-owned private equity firms frequently engage in coinvestments with other private equity firms. The coinvestment strategy allows them to mitigate risks and exchange valuable information and resources. Which types of partners do state-owned private equity firms typically collaborate with? The existing literature built coinvestment partner selection models based on the traditional regression models and ignored the complexity of the network structure. This research analyzes cooperative relationships using exponential random graph models, considering both structural effects and node attributes. The empirical study of 4645 private equity firms operating in the Chinese private equity market shows that state-owned private equities are more likely to collaborate with foreign private equities and domestic private-owned private equities compared to collaborating with other state-owned private equities. Furthermore, in markets characterized by high marketization indexes, state-owned private equities demonstrate greater inclinations to partner with foreign and domestic private-owned private equities. When state-owned private equities allocate their investments to high-tech industries, their likelihood of collaborating with foreign private equities increases.